Persepsi Konsumen terhadap Atribut Produk Susu Jagung ZeaGrain dengan Metode Importance Performance Analysis (IPA) - Siti Fayyaza Azzahra; Kamila Septianda Azura; Muhammad Dzaky Akmal Khair; Garcinia Dewi Safitri; Nurfitri Cahyaningtias; Khoirul Aziz Husyairi; Maulania Rahma Azzahra (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2026)
The development of value-added corn-based beverages representation an emerging opportunity within the agribusiness sector, particularly for student-led entrepreneurial initiatives seeking to utilize local agricultural resources. This study examines consumer perceptions of Zeagrain corn milk, a sweet-corn-derived drink positioned as a healthy, practical, and affordable alternative within the ready-to-drink market segment. The research aims to identify key attributes influencing consumer interest, evaluate perceived product performance, and assess the potential competitiveness of Zeagrain as a new agribusiness product. Data were collected using an online quantitative survey targeting respondents aged 17–35 years who represent potential urban consumers. The questionnaire measured demographic characteristics, consumption patterns of similar beverages, perceived importance and performance of product attributes, and purchase intention. The findings are expected to provide insights into consumer expectations regarding taste, packaging, nutritional value, and price. The results further serve as empirical input for improving product development strategies and enhancing the market readiness of Zeagrain. Ultimately, this study contributes to strengthening the commercialization prospects of corn-based beverages and supports innovation efforts among young agripreneurs seeking to optimize local commodities.